Azadirachtin disrupts ecdysone signaling and alters sand fly immunity - Cecilia Stahl Vieira; Sara Bisogno; Marco Salvemini; Erich Loza Telleria; Petr Volf (Parasites & Vectors)
Abstract Background Leishmaniasis is a group of neglected vector-borne diseases transmitted by phlebotomine sand flies. Leishmania parasites must overcome various defenses in the sand fly midgut, including the insects’s immune response. Insect immunity is regulated by the ecdysone hormone, which binds to its nuclear receptor (EcR) and activates the transcription of genes involved in insect immunity. However, the role of ecdysone in sand fly immunity has never been studied. Phlebotomus perniciosus is a natural vector of Leishmania infantum; here, we manipulated its neuroendocrine system using azadirachtin (Aza), a natural compound known to affect ecdysone synthesis. Methods Phlebotomus perniciosus larvae and adult females were fed on food containing either Aza alone or Aza plus ecdysone, and the effects on mortality and ecdysis were evaluated. Genes related to ecdysone signaling and immunity were identified in P. perniciosus, and the expression of antimicrobial peptides (AMPs), EcR, the ecdysone-induced genes Eip74EF and Eip75B, and the transcription factor serpent were analyzed using quantitative polymerase chain reaction (PCR). Results Aza treatment inhibited molting of first-instar (L1) larvae to L2, with only 10% of larvae molting compared to 95% in the control group. Serpent and Eip74EF, attacin, defensin 1, and defensin 2 genes were downregulated by Aza treatment in larvae. Similarly, Aza-treated adult females also presented suppression of ecdysone signaling-related genes and the AMPs attacin and defensin 2. Notably, all gene repression caused by Aza was reversed by adding ecdysone concomitantly with Aza to the larval or female food, indicating that these genes are effective markers for ecdysone repression. Conclusions These results highlight the critical role of ecdysone in regulating the development and immunity of P. perniciosus, which potentially could interfere with Leishmania infection. Graphical Abstract